2007
DOI: 10.1016/j.biomaterials.2007.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Epithelialization of hydrogels achieved by amine functionalization and co-culture with stromal cells

Abstract: (2007). Epithelialization of hydrogels achieved by amine functionalization and co-culture with stromal cells. Biomaterials, 28 (35), 5319 -5331. The aim of this study was to develop a hydrogel which would be suitable for corneal cell re-epithelialization when used as a corneal implant. To achieve this, a series of hydrogels were functionalized with primary amines by post-polymerization reactions between amine compounds and glycidyl ether groups attached to the hydrogels. We report a strong correlation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…However, it is the denuded matrix of the wound surface that carries the memory of what epithelial type should reside on it, and in wound healing, the matrix determines whether normal epithelial cells would or would not be prone to populate the wound area. Therefore, considerable effort is made in engineering instructive signals into substrates that would enhance epithelialization, using the methods ranging from soaking matrices with growth factors, through chemical matrix surface activation, up to the use of whole organisms to make changes in wounded tissues, such as medicinal maggot application (119,120). Cell memory and sensitivity to mechanical stimuli has been recently used in promising studies of acute and chronic wound epithelialization with the use of ultrasound and shock waves, and are now entering phase III clinical evaluation (121).…”
Section: Organ Level: Integration Of All Memory Mechanismsmentioning
confidence: 99%
“…However, it is the denuded matrix of the wound surface that carries the memory of what epithelial type should reside on it, and in wound healing, the matrix determines whether normal epithelial cells would or would not be prone to populate the wound area. Therefore, considerable effort is made in engineering instructive signals into substrates that would enhance epithelialization, using the methods ranging from soaking matrices with growth factors, through chemical matrix surface activation, up to the use of whole organisms to make changes in wounded tissues, such as medicinal maggot application (119,120). Cell memory and sensitivity to mechanical stimuli has been recently used in promising studies of acute and chronic wound epithelialization with the use of ultrasound and shock waves, and are now entering phase III clinical evaluation (121).…”
Section: Organ Level: Integration Of All Memory Mechanismsmentioning
confidence: 99%
“…(12) However, it was also shown, (12,14) as well as by Lin et al, (15) Our previous work showed that low molar mass (Mn < 2700 g mol -1 ) PBMA with carboxylic acid end groups (PBMA-COOH) was cytotoxic. (16) However, here we have shown that it is possible to produce PBMA-COOH with a low number average molar mass (Mn = 1400 g mol -1 ) that is not toxic to either human dermal fibroblasts or human renal epithelial cells provided the low molar mass material is diluted with higher molar mass material: i.e.…”
Section: Human Renal Epithelial Cells (Hrepc)mentioning
confidence: 84%
“…It was shown that coatings formed from PBMA-COOH were good substrates for supporting the culture of HDF and HREpCs. Following on from other previous work involving hydrogel membranes with primary amine functionality (12,14) the work reported here shows that primary amine-functional materials can be used to support epithelial cells but not fibroblasts. Our early work had provided some indication that coculture with stromal cells was advantages to supporting human corneal epithelial cells (HCECs) on amine-functional hydrogels but latter work by use (14) showed that this was not the case and that epithelialisation with HCECs was achieved with monoculture.…”
Section: Human Renal Epithelial Cells (Hrepc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging technologies to enhance the tissue response have involved the development of modified surfaces. This has involved the production of biomimetic surfaces either using synthetic analogues [9] or covalent binding of biological molecules, for example, collagen I to synthetic polymers such as polyethylene glycol/polyacrylic acid copolymers and N-isopropylacrylamide [10]. The cosmetic results from this approach are poor and thus there would be significant advantages in the development of a synthetic tissue equivalent.…”
Section: Cornea and Conjunctivamentioning
confidence: 98%